Cycling Behavior of NCM523/Graphite Lithium-Ion Cells in the 3–4.4 V Range: Diagnostic Studies of Full Cells and Harvested Electrodes. Issue 1 (22nd September 2016) - Gilbert, James A.; Bareño, Javier; Spila, Timothy; Trask, Stephen E.; Miller, Dean J.; Polzin, Bryant J.; Jansen, Andrew N.; Abraham, Daniel P.
Abstract : Energy density of full cells containing layered-oxide positive electrodes can be increased by raising the upper cutoff voltage above the present 4.2 V limit. In this article we examine aging behavior of cells, containing LiNi0.5 Co0.2 Mn0.3 O2 (NCM523)-based positive and graphite-based negative electrodes, which underwent up to ∼400 cycles in the 3–4.4 V range. Electrochemistry results from electrodes harvested from the cycled cells were obtained to identify causes of cell performance loss; these results were complemented with data from X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectroscopy (SIMS) measurements. Our experiments indicate that the full cell capacity fade increases linearly with cycle number and results from irreversible lithium loss in the negative electrode solid electrolyte interphase (SEI) layer. The accompanying electrode potential shift reduces utilization of active material in both electrodes and causes the positive electrode to cycle at higher states-of-charge. Full cell impedance rise on aging arises primarily at the positive electrode and results mainly from changes at the electrode-electrolyte interface; the small growth in negative electrode impedance reflects changes in the SEI layer. Our results indicate that cell performance loss could be mitigated by modifying the electrode-electrolyte interfaces through use of appropriate electrode coatings and/or electrolyte additives.